The Impact of Corporate Social Responsibility (CSR) on Sustainable Performance in an Organization. (Case Study of Volab Limited, Lagos State, Nigeria) - Edu J. USENDIAH; Rowland E. K. WORLU; Toyosi D. ODUNMORAYO; Somto J. OKOLO; Ejiro G. UKPEIBO (Communications of International Proceedings, 2021)
Change is inevitable as organizations grow and develop. There is therefore an increasing and revolving change on how things are done for better implementation of organizational goals which results into organizational image. Employers are discovering new ways to keep employees’ motivated and creative, while giving back and interacting with the community and business environment that gave the opportunity through CSR. This research aims to analyze the significant effect of Corporate Social Responsibility (CSR) on sustainable performance in an organization, previous studies  from 2017- 2019 have shown the relationship using various variables to measure its impact on the firm’s performance; though none has given a substantial evidence on the limiting condition in the Nigeria business environment, based on review of social emotional wealth theory and stewardship theory, this paper account for the aforesaid research gap. For this research study, the quantitative method was used in the selection of respondents and collection of data. A random sample size of 70 respondent was required to answer the questionnaire out of the entire population of 82. The result confirmed that ethical responsibility has a positive correlation with innovative process and employee performance: both economic responsibility and economic growth has a positive relationship with legal responsibility and operational excellence also to be a positive relation, which results into organizational growth, nevertheless, it may not be a necessary influence on the firm’s value despite its numerous benefits. These findings show that organization needs to measure performance with proper key performance index (KPI) in other to operate effectively and efficiently and ensuring proper oversight, individual, organization and economic benefits of CSR.
Keywords: Corporate Social Responsibility; Environmental vitality; Operational excellence; Innovative processes.